Profile of Traditional Fishermen on the Barito River - Munawarah, Madinatul; Nur’aini, Fatwa; Jumriani, Jumriani; Rahmia, Sovia Husni; Syarifuddin, Syarifudin (Universitas Lambung Mangkurat, 2024)
Fishermen are residents who do the work of looking for fish to meet their living needs. The fishing gear used is a simple fishing tool that is still traditional, these fishermen are trying to meet their living needs, in an era that is increasingly advanced. These traditional fishermen look for fish in the Barito River. With traditional fishing gear, these river fishermen are trying to find luck in catching fish. These traditional fishermen gain knowledge in going to sea from the teachings of their previous parents. The purpose of this study is to describe the profile of traditional fishermen and their fish catches in the Barito River. Qualitative methods and descriptive approaches used by researchers. This research is located in Anjir Village, Serapat Muara. The instrument for writing this study is the researcher himself and the data collected by the data collection techniques used are observation, interviews and documentation. The subject of this study is fishermen in Anjir Serapat Muara Village. The results of the research are that fishermen in Anjir Serapat Muara village are traditional fishermen both in terms of tools, materials and transportation used. They go to sea because it is done from generation to generation. The catch of this traditional fisherman is still small. Because by using simple fishing gear, the catch of fish is still minimal. The conclusion of this study is that in Anjir Serapat Muara Village, there are people who work as river fishermen who use fishing gear and simple transportation to sea. Fishermen have the knowledge to go to sea to find fish obtained by fishermen from their parents who have been taught since childhood and have been passed on until now to meet their needs.